2021
DOI: 10.1111/crj.13372
|View full text |Cite
|
Sign up to set email alerts
|

Use of GLP1RAs and occurrence of respiratory disorders: A meta‐analysis of large randomized trials of GLP1RAs

Abstract: BACKGROUNDAlthough there have been animal studies exploring the effects of glucagon-like peptide-1 receptor agonists (GLP1RAs) on pulmonary disorders, no large human studies have been designed to evaluate the efficacy of this drug class in the primary and secondary prevention of respiratory disorders. The superiority of GLP1RAs over placebo in cardiorenal outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In mice, liraglutide attenuated bleomycin-induced pulmonary fibrosis, ovalbumin (OVA)-induced chronic airway inflammation, and lipopolysaccharide (LPS)-induced acute lung injury (ALI) [7][8][9]. In a meta-analysis of large clinical trials investigating the cardiorenal benefits of GLP-1R agonists in T2D, there was a trend towards reduction of reported pulmonary adverse events in the GLP-1R agonist treatment groups [10]. While overall low incidence of respiratory disorders in these studies resulted in low statistical power, outcomes suggested benefits of GLP1-R agonist use in respiratory disease beyond that of glycemic control.…”
Section: Beyond Diabetesmentioning
confidence: 99%
“…In mice, liraglutide attenuated bleomycin-induced pulmonary fibrosis, ovalbumin (OVA)-induced chronic airway inflammation, and lipopolysaccharide (LPS)-induced acute lung injury (ALI) [7][8][9]. In a meta-analysis of large clinical trials investigating the cardiorenal benefits of GLP-1R agonists in T2D, there was a trend towards reduction of reported pulmonary adverse events in the GLP-1R agonist treatment groups [10]. While overall low incidence of respiratory disorders in these studies resulted in low statistical power, outcomes suggested benefits of GLP1-R agonist use in respiratory disease beyond that of glycemic control.…”
Section: Beyond Diabetesmentioning
confidence: 99%
“…To our knowledge, GLP-1-based drugs have not been utilized in clinical trials for ALI. Nevertheless, as mentioned above, a very recent retrospective study has shown that the utilization of GLP-1-based drugs reduced trends in the risks of pneumonia, in addition to asthma and COPD 131 . Extensive investigations have, however, been conducted in ALI animal models, mainly with intratracheally LPS administration in mice 143 .…”
Section: Glp-1-based Drugs In Airway Diseases and Lung Injury Studiesmentioning
confidence: 98%
“…In a meta-analysis study, Wei and colleagues 131 have reported that the utilization of GLP-1-based drugs showed reduced trends in the risks of nine categories of respiratory diseases, including pneumonia, bronchitis, pulmonary fibrosis, asthma, and COPD. However, GLP-1-based drug utilizations were shown to increase trends in interstitial lung disease.…”
Section: Glp-1-based Drugs In Airway Diseases and Lung Injury Studiesmentioning
confidence: 99%
“…In a study of meta-analysis, Wei and colleagues have reported that the utilization of GLP-1-based drugs showed reduced trends in the risks of nine categories of respiratory diseases, including pneumonia, asthma, and COPD. However, GLP-1 based drug utilizations were shown to increase trends in interstitial lung disease (104). In a recent retrospective cohort study, Foer and colleagues compared rates of asthma exacerbations and symptoms between patients with T2D and asthma prescribed GLP-1RAs and those prescribed sodiumglucose cotransporter-2 (SGLT-2) inhibitors, or DPP-4 inhibitors, or sulfonylureas, or basal insulin.…”
Section: Glp-1 Based Drugs In Lung Injury Studiesmentioning
confidence: 99%
“…To our knowledge, GLP-1-based drugs have not been utilized in clinical trials for ALI. Nevertheless, as mentioned above, a very recent retrospective study has shown that the utilization of GLP-1 based drugs reduced trends in the risks of pneumonia, in addition to asthma and COPD (104). Intensive investigations have, however, been conducted in ALI animal models, mainly with intratracheally LPS administration in mice (123).…”
Section: VII Studies In Acute Lung Injurymentioning
confidence: 99%